Greenwashing: Really Green Accounting or Claim Issued? - Lukmana putra, Indra; Nurefa Maulana (Universitas Palangka Raya, 2025)
Greenwashing has been a major concern in discussions on sustainability, where companies often claim environmentally friendly practices that are not always backed up by concrete actions. This research aims to determine whether greenwashing truly reflects sustainability or is just a marketing tactic. The method used analyzes literature and case studies from various industries over the period 2021-2024. The research found that greenwashing is more often used as a corporate image strategy than an actual commitment to sustainability. The results show that many companies utilize uncertain and less transparent environmental claims, which ultimately misleads consumers and hinders real progress in sustainable business practices. The findings emphasize the importance of stricter regulation and clearer reporting to ensure that sustainability claims truly reflect actions that support the environment. This research lies in highlighting the prevalence of greenwashing, which can inform policymakers and regulatory bodies about the need for stricter regulations and clearer reporting standards to protect consumers and promote genuine sustainability.The research is limited by its focus on the 2021-2024 period and lacks clarity on specific industries or regions, which may affect its generalizability. It relies on secondary sources without primary data, such as interviews or surveys, potentially missing emerging trends or firsthand insights into greenwashing practices. Keywords: Corporate Image Strategy; Greenwashing; Sustainability.